The Impact of Project-Based Blended Learning on User Interface Wireframe Learning Outcomes - Irfansyah Bayu Putra Pamungkas; Rusijono (JTP - Jurnal Teknologi Pendidikan, 2025)
The 2022 PISA (Programme for International Student Assessment) scores show that Indonesia's achievements in reading literacy, mathematics (numeracy), and science have declined compared to PISA 2018. In general, mathematics scores fell from 379 (2018) to 366 (2022), reading scores fell from 371 (2018) to 359 (2022), and science scores fell from 396 (2018) to 383 (2022). These scores are below the OECD average (around 480 for each subject), meaning that Indonesian students' abilities are still far behind global standards. This study aims to determine the effect of implementing Project Based Blended Learning (PjB2L) on learning outcomes for wireframe material in the User Interface (UI) subject for 11th grade students at SMK IPIEMS Surabaya. A quantitative method with a posttest-only control design was applied. The sample was divided into control and experimental groups. SPSS was used to test the validity and reliability of the instruments, where all items were proven to be valid and reliable (Cronbach's Alpha > 0.60). The Shapiro-Wilk test showed that the data were normally distributed (Sig. 0.200 > 0.05), while homogeneity was indicated by a significance value of 0.237 > 0.05. A t-value of -6.914, df 54, and Sig. (two tails) 0.000 < 0.05 were obtained from the independent sample t-test, confirming a significant difference between the control group and the experimental group. The effectiveness of PjB2L in improving wireframe learning outcomes was higher than that of conventional methods. It is recommended that educators implement Project Based Blended Learning (PjB2L) as a learning strategy because it has been proven to be more effective than conventional methods. Schools need to provide support in the form of technological facilities and teacher training, while students are expected to be more active, independent, and collaborative. Further research can expand the subjects and sample size to strengthen these findings.